2005
DOI: 10.1044/cicsd_32_f_85
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Feature Analysis as a Functional Therapy Tool

Abstract: Semantic feature analysis (SFA) is a therapeutic technique that is used for the treatment of naming deficits occurring with aphasia. Aphasia commonly impairs a person's ability to retrieve words easily, and speechlanguage pathologists (SLPs) often struggle to determine an effective means of facilitating this skill. SFA has been shown to improve naming of targeted items with generalization to control stimuli. SFA also teaches the individual with aphasia a process for accessing semantic networks and for self-cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The studies cover six different research areas. Nine studies investigated SFA with confrontation naming of nouns (Boyle, 2004;Boyle & Coelho 1995;Coelho, McHugh & Boyle, 2000;Davis & Stanton, 2005;DeLong, Nessler, Wright, & Wambaugh, 2015;Hashimoto & Frome, 2011;Massaro & Tompkins, 1994;Mehta & Isaki, 2016;Rider, Wright, Marshall, & Page, 2008). Two studies examined SFA with confrontation naming of verbs (Wambaugh & Ferguson, 2007;Wambaugh, Mauszycki, &Wright, 2014) and a further two tested SFA with confrontation naming of nouns and verbs (Kristensson, Behrns, & Saldert, 2015;Marcotte & Ansaldo, 2010).…”
Section: Study Selectionmentioning
confidence: 99%
“…The studies cover six different research areas. Nine studies investigated SFA with confrontation naming of nouns (Boyle, 2004;Boyle & Coelho 1995;Coelho, McHugh & Boyle, 2000;Davis & Stanton, 2005;DeLong, Nessler, Wright, & Wambaugh, 2015;Hashimoto & Frome, 2011;Massaro & Tompkins, 1994;Mehta & Isaki, 2016;Rider, Wright, Marshall, & Page, 2008). Two studies examined SFA with confrontation naming of verbs (Wambaugh & Ferguson, 2007;Wambaugh, Mauszycki, &Wright, 2014) and a further two tested SFA with confrontation naming of nouns and verbs (Kristensson, Behrns, & Saldert, 2015;Marcotte & Ansaldo, 2010).…”
Section: Study Selectionmentioning
confidence: 99%
“…This is an important finding that adds to current knowledge on maintenance of gains after SFA. In a recent systematic review of SFA studies (Efstratiadou et al, 2018), maintenance was reported for 58.18% of participants, but most of the included studies assessed maintenance in the short term, with only 2/21 studies assessing maintenance at 3 months or longer post therapy and only 1/4 participants in these two studies showing a positive effect (Davis & Stanton, 2005;Kristensson, Behrns & Saldert, 2015). Lastly, significant others perceived an improvement on participants' functional communicational skills at the follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all participants (19 of 23) who received SFA treatment maintained naming above baseline levels at follow-up testing, which occurred from 1 month to 1 year posttreatment. [33][34][35][36][37][38][39][40][41][42][43] A recent evidence-based systematic review of SFA reported that of 18 studies considered for review, 7 were eliminated because they combined SFA with other therapy methods or because they hybridized the SFA protocol. 44 Eight of the 11 remaining studies reported generalization of improved naming to untreated items.…”
Section: Semantic Feature Analysis For Objectsmentioning
confidence: 99%
“…44 Eight of the 11 remaining studies reported generalization of improved naming to untreated items. [33][34][35][36]40,41,43,45 All eight studies used imageable nouns as treatment targets and required participants to generate five to six semantic features for a target. Of the three studies that reported no generalization, one included treatment targets that were abstract (e.g., piece, charge, ingredients), 42 another focused solely on verbs, 46 and the third restricted participants to generating only three features per target.…”
Section: Semantic Feature Analysis For Objectsmentioning
confidence: 99%
See 1 more Smart Citation